MANAJEMEN KOMUNIKASI TERAUPETIK PADA PENYEMBUHAN PASIEN SKIZOFRENIA - Riyantie, Mayang; Barizki, Rezzi Nanda (Universitas Prof. Dr. Moestopo (Beragama), 2020)
The research objective was to determine the effectiveness of interpersonal communication between senior and junior nurses in the planning of therapeutic communication management for patient healing at the Islamic Mental Hospital, Klender Jakarta. The research method uses descriptive qualitative in the phenomenological tradition. Therefore, a dramaturgical element is used, regarding the symbolic world of senior and junior nurses on the front stage and the back stage. From the research, it was found that there was a communication disorder due to rivalry between junior and senior nurses. In fact, communicators are required not only theoretical and practical capabilities, but also the experience of the therapist. The dominant experience in this aspect of message management demands effective coordination. This is due to the diverse psychological spectrum of patients as communicants. In the back stage, nurses as communicators are demanded to be competent in making communication management planning. On the front stage, the effectiveness of coordination and construction of generating meaning in the minds of the communicants is also required. That is, psychologically, they must be ready, not bring any problems and motives when doing therapeutic communication, so that they can manage impressions that are patient, painstaking and full of willingness.